2022
DOI: 10.32615/bp.2022.016
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS shotgun proteomics reveals biochemical mechanisms of Paspalum fasciculatum tolerance to Pb-stress

Abstract: Paspalum fasciculatum Willd. ex Flüggé grows in mining soils which are Cd-and Pb-contaminated where it exhibits tolerance to Pb and the ability to extract Pb from these soils. To elucidate tolerance mechanisms to Pb-stress, liquid chromatography with tandem mass spectrometry (LC-MS/MS) was used to quantify changes in the accumulation of proteins in leaves. We identified 323 proteins involved in primary metabolism and response to biotic or abiotic stresses. Although proteins involved in the processes of photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted May 22, 2023. ; https://doi.org/10.1101/2023.05.18.541295 doi: bioRxiv preprint 3-3 protein were observed at 4 h and 8 h of Cu stress in Phanerochaete chrysosporium (Okay et al, 2020). In addition, proteomics data indicated that 14-3-3 proteins might participate in Pb stress mechanisms in Paspalum fasciculatum (Salas-Moreno et al, 2022a). Micromolar magnesium could mitigate the toxicity of Al through promoting the phosphorylation of VHA2 (PM H + -ATPase) and improving the interaction between VHA2 and 14-3-3b in Vicia faba.…”
Section: -3-3s Participate In Heavy Metal Stress Response and Detoxif...mentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted May 22, 2023. ; https://doi.org/10.1101/2023.05.18.541295 doi: bioRxiv preprint 3-3 protein were observed at 4 h and 8 h of Cu stress in Phanerochaete chrysosporium (Okay et al, 2020). In addition, proteomics data indicated that 14-3-3 proteins might participate in Pb stress mechanisms in Paspalum fasciculatum (Salas-Moreno et al, 2022a). Micromolar magnesium could mitigate the toxicity of Al through promoting the phosphorylation of VHA2 (PM H + -ATPase) and improving the interaction between VHA2 and 14-3-3b in Vicia faba.…”
Section: -3-3s Participate In Heavy Metal Stress Response and Detoxif...mentioning
confidence: 99%